Language awareness and the education of non-native English teachers in South America: TLA concept review and implications - Evelin Suij-Ojeda (Westcliff University, 2017)
Reflecting upon language allows teachers, not only to have a greater insight on how English, the language they teach works in the "real world", but also helps them design activities for their learners to discover language by themselves while, as stated by Bolitho (2003), promoting independent and critical thinking in their classrooms. This paper explores the implications and theoretical foundations of introducing Language Awareness activities as part of the curriculum in teacher education programs in South America. Because of its length, this paper does not intend to recommend a solution to the issue but analyses the theories that support the inclusion of TLA activities as part of the English Language teacher training and education curriculum. Besides, it forecasts the implications derived from such implementation and changes.